STUDI PUTUSAN HAKIM DALAM DISPENSASI KAWIN DI PENGADILAN AGAMA : PERSPEKTIF FILSAFAT HUKUM ISLAM - rifqi khairul anam (LPPM UNHASY, 2025)
This research is a literature study that examines marriage dispensations. The researcher investigates the legal regulations provided by the Religious Courts to potential brides and grooms who do not meet the age criteria stated in Law Number 1 of 1974. When considering marriage dispensations, the court takes into account many rules, such as the Marriage Law, Compilation of Islamic Law, Supreme Court Regulation no. 5 of 2019, and Minister of Religion Regulation no. 11 of 2007 about Marriage Registration. Various factors in life impact the judge's judgment to either grant or deny permission. One important factor to take into account is the age and level of personal maturity of the potential bride and groom. The judge assesses the degree to which they are prepared to enter into the institution of marriage. Another significant factor to consider is the element of health. The judge's decision is influenced by the health condition of the potential bride and groom, which is the third factor to consider. Additionally, economic factors are included as they might impact the longevity of a marital union due to their influence on financial stability. The court guarantees that every decision is made after a comprehensive review of the prospective bride and groom's condition, taking into account numerous variables. Marriage dispensation is not only a procedural requirement, but a policy that carefully takes into account all facets of life.